Sacrifice of Humans and Animals in Religious Practices (International Journal of Innovative Research in Engineering & Management, 2023)
The main practice of the ancient  Mediterranean religion was the sacrifice of animals,  including the slaughter and the gifting of one or more  animals. Traditional blood offerings were part of a life and  death cycle that should thrive both animals and humans.  Throughout the Empire Christians and pagans alike rejected  such sacrifices. This article discusses the pagan and  Christian critiques of Greco-Roman blood sacrifices.  Authority was founded on the cultural killing of animals  and the distribution and eating of their flesh in an old  sacrificial discourse. In the new soteriological discourse,  power was founded on a symbolic capital of moral and  physical pureness and intellectual insights, and the goals of  spiritual perfection and redemption. Some of the religions  that participated in the new conversation, although  Christianity banned it, continued to practice animal  sacrifice. Direct human body screening for medicine and  future study, as well as electronic medical data, are both  useful in minimizing biomedical research sacrifice for  animals. These techniques and strategies of research may be  more economical and applied to a range of human health  issues.
Keywords: Animal Sacrifice; Bones; Civilization; Human Sacrifice; Religion